Analysis of manganese deposits from the Alps - Sabatino, Nadia; Neri, Rodolfo; Bellanca, Adriana; Jenkyns, Hugh C; Masetti, D; Scopelliti, G (Supplement to: Sabatino, N et al. (2011): Petrography and high-resolution geochemical records of Lower Jurassic manganese-rich deposits from Monte Mangart, Julian Alps. Palaeogeography, Palaeoclimatology, Palaeoecology, 299(1-2), 97-109, https://doi.org/10.1016/j.palaeo.2010.10.039, 2011)
Deposits with unusually high Mn contents sampled at Monte Mangart in the Julian Alps include organic-rich marlstone and black shale with interbedded manganoan and siliceous limestone, which were deposited during the early Toarcian Oceanic Anoxic Event. Mn enrichment during that period has been related to global sea-level change coincident with increasing subsidence rate. The formation of Fe-Mn nodules, marking a hardground at the base of the Monte Mangart section, seems to be triggered by release of Mn from remote hydrothermal vents into a region of relatively elevated submarine topography where oxidizing conditions prevailed. However, very high Mn contents in carbonate phases above the hardground imply an additional diagenetic source of this element in the lower part of this section. The whole stratigraphic sequence (ca 30 m) displays a transition from Mn-rich (up to 8.8%) sediments, in the lower part, to Mn-poor (less than 1.8%) sediments in the middle and upper parts. The drastic decrease in Mn content's up-section is accompanied by a clear decrease in the mean size of pyrite framboids, indicating more intense anoxia/euxinia in the water column. In the presence of Mn2+, conditions of high alkalinity induced precipitation of Mn carbonates during early diagenetic processes. Negative [delta]13Ccarb values coincident with high Mn contents indicate involvement of organic matter in the mineralization process. The striking similarity of Ce/Ce* and Mn profiles demonstrates that, consistent with redox-chemistry of Mn and Ce under anoxic conditions, Ce3+ and Mn2+ were mobilized and released into pore water where precipitation of Mn carbonates occurred.